Assessment of the Efficiency of Investment Activity of Insurance Companies in the Republic of Armenia. - Safaryan, Norayr; Ghazaryan, Lusine (Bulletin of Yerevan University G: Economics, 2025)
The article analyzes the structure and efficiency of investment activities of non-life insurance companies operating in the insurance market of the Republic of Armenia, based on which it is recorded that investment policy plays a key role in ensuring the financial stability, liquidity and profitability of companies. From the investment indicators of the six insurance companies studied for 2020–2024, including the investment activity ratio, profit sensitivity ratio, ROE and ROA, it becomes obvious that the efficiency of investments varies significantly between different companies and periods, due to management approaches and the market situation. The recorded trends and asymmetries indicate the need to revise asset management strategies. This study is important from the point of view of the development of the insurance sector, since the investment policy of insurance companies significantly affects their financial stability and competitiveness. Assessment of the Efficiency of Investment Activity of Insurance Companies in the Republic of Armenia